Stress-coping skills and neuroticism in apical ballooning syndrome (Takotsubo/stress cardiomyopathy). Issue 1 (5th February 2016) - Scantlebury, Dawn C; Rohe, Daniel E; Best, Patricia J M; Lennon, Ryan J; Lerman, Amir; Prasad, Abhiram
Abstract : Introduction: Apical ballooning syndrome (ABS) is typically associated with an antecedent stressful situation. Affected patients have been reported to have higher frequencies of premorbid affective disorders. We hypothesised that patients with ABS would have elevated levels of neuroticism (tendency to experience negative affect) and greater vulnerability to stress. Methods: In this cross-sectional study, all active participants in the Mayo Clinic ABS prospective follow-up registry were invited to complete the third edition of the NEO Personality Inventory (NEO-PI-3). The NEO-PI-3 is the universally accepted measure of the 'Five-Factor Model' of personality. Inventory responses were scored using the NEO-PI-3 computer program and the data were compared with US normative sample used in standardisation of the inventory. Significance was set at 0.0014 to account for multiple comparisons. Results: Of 106 registry participants approached, 53 completed the inventory. There was no difference in age, gender, time from ABS diagnosis, type of antecedent stressor (emotional, physical or none) or severity of initial illness between the responders and non-responders. Responders had mean Neuroticism T-scores of 48.0±10.6 (95% CI 45.1 to 50.9); p=0.18, when compared with the normal mean of 50. There was also no significant difference in the facet scale of Vulnerability: 46.9±8.4 (44.6 to 49.2), p=0.038, at α=0.0014. Conclusions: Contrary to our hypothesis, patients with ABS do not manifest higher levels of neuroticism and do not have greater vulnerability to stress than the general population. These findings have implications for the clinicians' perception of, and approach to, patients with ABS.